Development of a Digital Marketing Advertising Film Creation Model for Generation Z - Julakarn, Sutee (Journal of Information and Learning [JIL], 2023)
The objectives of this research were 1) to develop a digital marketing advertising film creation model for generation z, and 2) to evaluate the effectiveness of digital marketing advertising films for generation z. The sample of 400 people aged 18 to 21 years in Khon Kaen University. Data were collected by using a media performance assessment questionnaire and were analyzed using mean and standard deviation. The results showed that 1) the DDT model, a digital marketing advertising film creation model for generation z, consists of three key processes: data (fundamental information about goods and services, management of product and service data, competitor information, consumer behavior, and communication objectives), design (creating content that effectively communicated with the target audience, evoking a desire to share or transmit the message), and techniques (presentation methodologies that facilitated audience understanding and engagement by using up-to-date stories aligned with viewer behavior). The DDT model was tested to create five advertising clips, categorized into two types: short ad series and standalone short ads. The evaluation of advertising film effectiveness has two aspects: attitude towards advertising films and opinions on advertising films. Overall, the highest level of preference was for the BuBu ads, with a mean of 4.54 and a standard deviation of 0.54, and McDonalds ads, with a mean of 4.52 and a standard deviation of 0.59.